The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s1806-66902014000100004
|View full text |Cite
|
Sign up to set email alerts
|

Growth, gas exchange and yield of peanut in frequency of irrigation

Abstract: -This study was conducted to evaluate the effect of different irrigation frequencies on growth, gas exchange and yield of the peanut (Arachis ypogea L). The experiment was conducted in the field using the experimental design of randomized blocks with five treatments, five replications with four plants per plot. The treatments were composed: F2 = (irrigation every 2 days), F4 = (irrigation every 4 days), F6 = (irrigation every 6 days), F8 = (irrigation every 2 days) and F10 = (irrigation every 10 days). At 60 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
5
0
7
Order By: Relevance
“…The irrigation frequency, defined by the interval between two successive irrigations should be used in a way so as not to compromise the water needs of the plants in their different phenological stages (Sousa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The irrigation frequency, defined by the interval between two successive irrigations should be used in a way so as not to compromise the water needs of the plants in their different phenological stages (Sousa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Com relação à altura das plantas, não houve interferência dos fatores em estudo, com altura média de 35,9 cm, valores próximos aos encontrados por Sousa et al (2014) trabalhando com amendoim ereto na mesma região, no município de Fortaleza-CE, em função da frequência de irrigação, obtiveram maiores valores de altura para o intervalo de dois dias entre as irrigações, com altura de aproximadamente 38 cm. Na Tabela 2, verifica-se que a única variável que apresentou diferença significativa para todos os fatores foi o número de vagens por planta para os fatores sistema de plantio e adubação (p<0,01), e cultivar (p<0,05).…”
Section: Resultsunclassified
“…Subramaniam and Maheswari (1990) reported that leaf water potential, transpiration rate and photosynthetic rate decreased progressively with increasing duration of water stress in peanut. The gas exchange variables at 60 DAS were affected by various frequency of irrigation and the best results for gaseous exchange characteristics were gained by highest irrigation frequency tested (every 2 days) in peanuts (Sousa et al 2014). The transpiration efficiency (TE) is the WUE int (the ratio of instantaneous CO 2 assimilation (A) to transpiration at leaf level.…”
Section: Discussionmentioning
confidence: 99%